Analysis of FMRF-amide effects on Aplysia bursting neurons - Ruben, P (J Neurosci, 1986)
The peptide L-phenylalanyl-L-methionyl-L-arginyl-L-phenylalaninamide (FMRF-amide) was pressure-applied onto the somata of bursting neurons L4 and L6 in the Aplysia abdominal ganglion. FMRF-amide causes a biphasic response, first depolarizing and then hyperpolarizing the neuron. In voltage-clamp experiments, FMRF-amide induces an inward current that begins 100–200 msec after applying the peptide and peaks in 2–10 sec. This is followed by an outward current that begins with a latency of 2–5 sec and peaks in 15–65 sec. The entire response lasts 1– 5 min. Experiments were done to separate the two currents induced by FMRF-amide on the basis of ion selectivity and kinetics and to determine their I(V) relationships. The currents were studied using a method to quickly measure I(V) curves. The inward current is caused by a conductance increase and has a reversal potential of approximately +18 mV. This current depends on the concentration of extracellular Na ions but not Ca, Cl, or K ions and is insensitive to tetrodotoxin, hexamethonium, and curare. The outward current is caused by a conductance increase and has a reversal potential of approximately -61 mV, which is similar to the reversal potential of the fast, transient K current (IA) in the same cells. This current is sensitive to changes in the external K ion concentration but not to changes in Cl, Ca, or Na concentration. The outward current is partially blocked by 1 mM 4- aminopyridine but not TEA or curare. Neither current is significantly voltage dependent within the range from -70 to -40 mV.(ABSTRACT TRUNCATED AT 250 WORDS)